Kisebbségvédelem, avagy az Európai Unió reakciói a kisebbségi jogsértésekre és a kommunizmus bűntetteire - Bocskor Andrea; Бочкор Андрея („RIK-U” Kiadó, 2017)
A XX. századi történelem számos olyan konfliktust, területi vitát és háborút hozott az emberiségnek, melyek következtében több millió ember volt kénytelen elhagyni szülőföldjét, deportálták, bebörtönözték, életét vesztette, ezek egy része valamely őshonos, etnikai, kulturális vagy nyelvi kisebbségi csoporthoz tartozott. A felsorolt bűnöket a kisebbségi közösségekkel szemben javarészt a totalitárius rendszerek követték el, így ezek felszámolása a túlélésnek és megerősödésnek, illetve az igazságszolgáltatásnak és a bűnösök megbüntetésének reményét is keltették a meghurcolt és megtizedelt közösségekben. A Szovjetunió felbomlása jelentős mérföldkő volt abból a szempontból, hogy a szovjet uniformizáló rendszer által egységbe tömörített és elnyomott nemzetiségek, valamint az egykori Keleti Blokk országai kitörhettek Moszkva teljhatalmú irányítása alól, történetük ezáltal egy új szakaszba lépett.

Abstract. The 20th century witnessed two world wars, numerous territorial and ethnic conflicts that lead to human tragedies on personal and community level either. Basing on historical research we can state that the most severe crimes against humanity were committed by totalitarian regimes: the Communizm, the Naczi and the Fascist regimes. These crimes are still not investigated completely and even the victims are not rehabilitated in many countries. Since the enlarging of the European Union by Central-European countries the issue of the minority rights and their protection is constantly on the agenda. In the 1990th the EU seemed to have the political will to find solutions and to define the minimum standards of the minority rights, e.g. by formulating the Coppenhagen Criterias, but the experience showes that it is not enough. Crimes of totalitarian regimes, especially of the Communizm, against humanity, including those commited against minority communities are still "swept under the carpet" in the EU, as there is no legal framework for dealing with it. Since 2008 Prague Declaration there are initiatives of some member states or politicians, members of the Europian and National Parliaments to raise the issue on the EU level, and there are some achievemnts, e.g. proclamation of 23 August as European Day of Remembrance for Victims of Stalinism and Nazism, but we have to do more efforts in order to reach reconciliation.
Minority protection with regard to the reactions of the European Union to the minority rights affections and the crimes of communism
https://kmf.uz.ua/hu/kiadvanyaink/hadifogsag-malenkij-robot-gulag-karpat-medencei-magyarok-es-nemetek-elhurcolasa-szovjetunio-hadifogolyes-kenyszermunkataboraiba-1944-1953/
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00004138
Keywords: kisebbségvédelem; Európai Unió; kisebbségi jogsértés; kommunizmus